What does it take to facilitate the integration of clinical practice guidelines for the management of low back pain into practice? Part 1: A synthesis of recommendation. Issue 8 (8th June 2021) - Longtin, Christian; Décary, Simon; Cook, Chad E.; Tousignant‐Laflamme, Yannick
Abstract: Background: Despite the emergence of multiple clinical practice guidelines (CPGs) for the rehabilitation of low back pain (LBP) over the last decade, self‐reported levels of disability in this population have not improved. This may be explained by the numerous implementation barriers, such as the complexity of information and sheer volumes of CPGs. Objectives: The purpose of this study was to summarize the evidence and recommendations from the most recent and high‐quality CPGs on the rehabilitation management of LBP by developing an infographic summarizing the recommendations to facilitate dissemination into clinical practice. Methods: We performed a systematic review of high‐quality CPGs with an emphasis on rehabilitation approaches. We searched major health‐related research databases (e.g., PubMed, CINAHL, and PEDro). We performed quality assessment via the AGREE‐II instrument. Contents of the CPGs were synthesized by extracting recommendations, which were then compared to one another to identify consistencies based on an iterative evaluation process. Results: We identified and assessed 5 recent high‐quality CPGs. We synthesized 13 recommendations on the rehabilitation management of LBP (2 for screening procedures, 3 for assessment procedures, and 8 involving treatment approaches) and 2 underlying principles were highlighted. These results were then synthetized and illustrated in a concise infographic that serves as a conceptual roadmap that identifies the specific behavior changes (i.e., adoption of CPGs' recommendations) rehabilitation professionals should adopt in order to integrate an evidenced‐based approach for the management of LBP. Conclusions: We systematically reviewed the literature for CPGs' recommendations for the physical rehabilitation management of LBP and synthesized the information through an infographic.